THE MULTILINGUAL TURN IN SLA AND THE PRAXIS OF DECOLONIAL FISSURE - Setiono Sugiharto (Journal of Cultura and Lingua, 2020)
Recent debates over the notion of the multilingual turn in applied linguistics in general and Second Language Acquisition (SLA) in particular clearly reflect the robustness of the notion in the fields. Yet, what is often ignored in the debate is the fact the notion itself is by nature problematic, and, as a consequence, the discussion of its realization in the fields of applied linguistics and SLA is fraught with disputes. In this article, I will first revisit the notion of the multilingual turn in order to show the contentious nature of the term, and then go on to suggest that we need to shy away from creating a division of labor between scholars from the global South and North, as has been propounded by Mendoza (2019); instead, we need to invest our efforts to ponder over more nuanced and situated actions which must be carried out by scholars from the global South to reform the above disciplines through “the praxis of decolonial fissure” (Walsh, 2018).